2019
DOI: 10.3168/jds.2018-15368
|View full text |Cite
|
Sign up to set email alerts
|

Space allowance influences individually housed Holstein male calves' age at feed consumption, standing behaviors, and measures of immune resilience before and after step-down weaning

Abstract: Many dairy calves in the southwestern regions of the United States are raised in wooden hutches with 1.23 m 2 of free space that house 3 calves individually. Producers claim that calves in hutch systems are not ready to wean and be placed in groups at the country-average age of 6 wk. Calves may remain in this individual housing system until as late as 10 wk of age. The objective of this study was to modify space allowance of hutches and evaluate weaning readiness using age at solid feed consumption, standing b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 65 publications
0
3
0
Order By: Relevance
“…Calves start ingesting feed at an earlier age, compared with when provided 1.25 m 2 (Hulbert et al., 2019 ) because their feeding and exploratory behaviours are facilitated…”
Section: Resultsmentioning
confidence: 99%
“…Calves start ingesting feed at an earlier age, compared with when provided 1.25 m 2 (Hulbert et al., 2019 ) because their feeding and exploratory behaviours are facilitated…”
Section: Resultsmentioning
confidence: 99%
“…The earliest age at which this procedure can be done is 40 days, as it can cause malnutrition if done earlier ( 96 ). In all the studies reviewed ( 103 , 108 , 109 ), this weaning is carried out up to 62 days.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, this type of housing may alleviate some of the negative aspects of weaning, as this stress is cushioned by social support (38,45,46), and less non-nutritive oral behaviours are observed (34). Finally, calves housed in pairs are better prepared to live in groups after weaning (47). However, studies have shown that pair-housing also has its limitations.…”
Section: Interaction With Congenersmentioning
confidence: 99%